THE ANALYSIS OF ENGLISH PLOSIVE CONSONANT SOUNDS ON YOUTUBES' CHANNEL - Rahman, Ananda Fathur; Pratiwi, Dwiyani (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to examine and analyze the pronunciation errors of English plosive consonants, especially the sounds /p/, /t/, /d/, and /k/, by Andovi Da Lopez in a rap cover music video on the SkinnyIndonesian24 Youtube channel. The type of research used is descriptive qualitative. The research data is in the form of Andovi Da Lopez's speech containing these plosive sounds, and the data source is a video uploaded on the SkinnyIndonesian24 Youtube channel. The data collection technique was carried out using the documentation study method. The collected data were then analyzed descriptively by identifying, classifying, and interpreting pronunciation errors of plosive sounds. The results of the study show that Andovi Da Lopez still has several weaknesses in pronouncing English plosive sounds. Specifically, it was found that Andovi Da Lopez still has weaknesses in pronouncing the sound /d/. In addition, the pronunciation of the sound /p/ often sounds like /b/, and the sound /t/ is pronounced following the pronunciation pattern of /d/. There are also several errors in pronunciation of the /k/ sound, such as not pronouncing it at the end of a word or replacing it with another sound.